DAMPAK ALGORITMA TIKTOK TERHADAP KONSUMSI MUSIK - Regina Rachmadayanti; Finella Andini; Valerie Vanora Susilo; Wahyu Sheilma Syahroni (Lembaga Penelitian dan Pengabdian Kepada Masyarakat Universitas Tarumanagara, 2021)
TikTok, a digital platform to share short videos is noted as one of the most popular apps nowadays. Trends are born in TikTok and influence other platforms, even the public in general. The virality factor draws people and music industry in as music is a core part of the app. As the pandemic strikes, the industry's main income from live performances was taken away and instead relies on digital streaming and sales. This article discusses the correlation between TikTok's algorithm and the consumption of music. TikTok tracks the watch time of each user, then recommends a video based on it. Many companies are born to create viral videos on TikTok. Blogs and interviews revealed that record labels could set up a collaboration with TikTok to spread a song using their influencers then TikTok could pull the trigger to put it everywhere using advertisements. On the other hand, another song could get popular naturally. The higher rate of new videos created using the popular track could increase it's position and streams in Spotify. Trends come and go, but artists stay. As the industry becomes more unsustainable day by day with